Proposta de modelo para avaliar a contribuição dos indicadores obtidos na análise do ciclo de vida sobre a geração de inovação na indústria - Luz, Leila Mendes da (2011)
In an increasingly competitive environment, innovation has become a fundamental element for competitiveness and, in this scenario the environmental issue has been stood out as a key differentiator for organizations. Consequently, sustainable development has gained a prominent position in the business and in addition to stimulating innovation; managers need to ensure good environmental performance of the organization. Due to this, evaluation techniques have been developed for the purpose of evaluating the environmental impact products have over the environment. One technique that has stood out is the Life Cycle Analysis (LCA) which covers the entire product lifecycle, and may assist in decision making within organizations. Thus, this paper has as its aim to propose a theoretical model to evaluate the contribution of the indicators obtained from Life cycle inventory on the generation of industry innovation. For this, in the theoretical reference it was discussed concepts related to the LCA, and the innovation potential of LCA for the generation of innovation. The method used in the research was deductive, using the methodological, qualitative, quantitative, exploratory and literature approach applied. In the model constructing, LCI indicators had been used related to natural resources, secondary raw materials, atmospheric emissions, liquid effluents, solid waste and the indicators of innovation: impact of innovation, innovation activities and information sources. These indicators were obtained by simulation based on data found in literature, being the LCI about the aluminum packaging for soda and the innovative, from the latest issue of Research on Technological Innovation of the Brazilian Institute of Geography and Statistics, for the sector of manufacturing metal packaging. The proposed model uses statistical methods to analyze the relationship between these two variables, being employed the tests: normality of the data, Pearson correlation, Spearman correlation, formulation of the regression equation and coefficient of determination. Besides the points of correlation it is possible to determine the percentage of variation among the dependent variables which can be explained by the independent variables. Into this way, the analysis gotten in the results showed a significant correlation between LCI indicators versus innovation indicators "innovative activities", indicating that all groups of indicators considered in the LCI study are somehow related to innovation through indicators related to innovation activities. Finally, it is possible to conclude that the application of the developed model will allow identifying points of correlation between the LCI and innovation that will enable organizations to guide actions in a more efficient and punctual way, which contribute to the generation of innovation in the product system.